Boosting supercapacitor efficiency with mixed metal-based activated carbon nanocomposites - Maria Shaheen; Farhat Saira; Abid Inayat; Syed Mustansar Abbas; Hameed Ullah; Sadia Khalid; Sana Sabahat; Saja A. Althobaiti; Nissren Tamam (Fuel, 2026)

Two-stage valorization of glycol-based waste fluids via Yarrowia lipolytica bioconversion and biomethane production - Katarzyna E. Kosiorowska; Michał Kozłowski; Habiba Khalid; Marcin Jasiak; Kacper Świechowski; Aleksandra Maria Mirończuk; Andrzej Białowiec (International Biodeterioration & Biodegradation, 2026)

Functional and structural characterization of the SARS-CoV-2 spike N481K mutation - Maria K. Smatti; Hebah Al-Khatib; Muhammad Suleman; Muna Nizar; Hala Abo Khalid; Ruaa Ismail; Gheyath K. Nasrallah; Hadi M. Yassine (Archives of Virology, 2026)
Background: Selective pressure drives SARS-CoV-2 evolution, with spike RBD substitutions shaping ACE2 binding and antibody escape. N481K RBD mutation emerged early in Qatar (2020) and later re-emerged globally, reaching near-fixation by 2024–2025, yet its functional significance remained unexplored. Methods: We analyzed the temporal and geographic circulation of N481K across > 17 million SARS-CoV-2 genomes (2020–2025). Structural effects were assessed using modeling, docking, and molecular dynamics. Functional impact was evaluated using VSV pseudovirus neutralization tests with sera from infected individuals (n = 48) and vaccinated cohorts: mRNA (n = 16), Sinopharm (n = 45), and AstraZeneca (n = 28). Results: N481K was detected in 4.14% (703,777/17,016,111) of global genomes and reached near-fixation (> 90%) in dominant Omicron lineages by 2024, with prevalence rising from 71.5% in early 2024 to 94.4% by week 36 of 2025. Structural analyses showed a 0.706 Å RMSD deviation and higher ACE2 docking affinity (–313 vs. − 308 kcal/mol) compared to the wild-type (WT) RBD. Molecular dynamics confirmed increased stability and lower binding free energy for N481K versus WT (–77.07 ± 0.90 vs. − 43.09 ± 0.98 kcal/mol). Among samples with detectable WT neutralization (n = 89), mean neutralization declined from 69.76% (WT) to 42.47% (N481K) (p

Multi-Species Probiotics Improve Health Performance and Alleviate Stress Responses of Rohu (Labeo rohita) in Inland Brackish Water Ponds - Habiba Jamil; Abdul Ghaffar; Fozia Afzal; Saima Naz; Ayesha Farooq; Maria Saeed Khan; Fuad M. Alzahrani; Khalaf F. Alsharif; Khalid J. Alzahrani; Qudrat Ullah (Probiotics and Antimicrobial Proteins, 2026)

Decoding rhizosphere microbiome assembly: a dual framework of environment-driven and host genetics-driven components for sustainable agriculture - Muhammad Ikram; Burhan Khalid; Kamran Haider; Maria Batool; Maaz Ullah; Muhammad Akif; Tao Deng; Jie Kuai; Zhenghua Xu; Jie Zhao; Jing Wang; Bo Wang; et al. (Plant and Soil, 2026)

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

Remediating Methylene Blue and Eriochrome Black T by Acid Activated Multiwalled Carbon Nanotubes - Sultan Muhammad; Zubaah Khalid; Maria Khan; Ammara Aftab; Muhammad Waseem (International Journal of Environmental Research, 2026)

First Detection of Lactococcus formosensis subsp. formosensis in Rainbow Trout ( Oncorhynchus mykiss ) in Europe - Silvia Colussi; Giuseppe Esposito; Khalid Shahin; Pier Luigi Acutis; Lucio Fariano; Claudio Ghittino; Maria Goria; Fabio Bondavalli; Paolo Ajmone Marsan; Giorgia Bignami; Elena Bozzetta; Marino Prearo; et al. (Journal of Fish Diseases, 2026)
Lactococcus garvieae , Lactococcus petauri and Lactococcus formosensis are etiological agents of piscine lactococcosis, a disease reported in Italy since the early 1990s and linked to significant aquaculture losses. To the best of our knowledge, this study reports the first detection of L. formosensis subsp. formosensis in farmed rainbow trout ( Oncorhynchus mykiss ) in Europe. In 2024, a total of 70 trout were sampled in the Piedmont region (Northern Italy), as part of a health monitoring programme. Bacteriological and molecular analyses showed the presence of L. garvieae in four fish (5.7%) and the identification of L. formosensis subsp. formosensis in one single fish exhibiting mild clinical signs via 16S‐23S rRNA ITS sequencing. Phylogenetic analysis confirmed the clustering of the isolate within the L. formosensis clade, clearly distinct from L. garvieae and L. petauri . Virulotype comparison showed greater similarity between L. petauri and L. formosensis subsp. formosensis , while the latter exhibited a distinct biochemical profile and was highly susceptible to antibiotics commonly used in aquaculture. Nevertheless, monitoring and advanced diagnostics are essential to clarify the role of this bacterium and to develop any necessary preventive and control measures.

Photoperiod and temperature: Key abiotic drivers of horticultural crop physiology in a changing climate - Muhammad Atiq Ashraf; Shumaila Nawaz; Uzma Bilal; Maria Abubakar; Shumaila Anam; Muhammad Azam; Burhan Khalid; Abdullah; Muhammad Asim; Rabbya Rayan Shah; Muhammad Ateeq (Biologia, 2026)

Photocatalytic removal of textile dyes: Analytical strategies for post-degradation evaluation - Md. Khalid Hossain Shishir; Md. Shoyeb Akand; Mohshin Maola; Maria Ferdusi Monira; Md. Rifat; Nafis Rahman Sayeem; Al Masud; Sukanta Mondal; Gazi Md. Arifuzzaman Khan (Desalination, 2026)

Mechanistic insight into inflammatory and oxidative stress ameliorating attributes of Atriplex crassifolia 70% ethanol extract against complete Freund’s adjuvant-induced arthritis - Jawaria Khurshid; Anam Iftikhar; Hamza Ahmad Odeibat; Eman Hassan Alshehri; Kiran Aslam; Maria Jaleel; Aymun Jawed; Muhammad Khalid Saeed; Rodney Luwor; Taha Muhammad; Mohammad Saleem; Mohamed Farouk Elsadek (Inflammopharmacology, 2025)

Correction: Pollen morphology of cucurbitaceae using microscopic techniques for accurate taxa identification - Haleema Sadia; Khafsa Malik; Rahmatullah Qureshi; Khalid Mehmood; Khushdil Khan; Ahmad Hassan; Shabir Ahmad; Hussain Shah; Huma Gul; Jawaher Alkahtani; Bandar Mohsen Almunqedhi; Rashid Iqbal; et al. (Genetic Resources and Crop Evolution, 2025)

Computational design and preparation of resorcinol imprinted hydrogel coated on IDE for electrochemical sensing of RS - Nimra Younas; Ghulam Mustafa; Mubushar Majeed; Khalid Pervaiz; Maria Saif (Analytica Chimica Acta, 2025)

Genome-wide association of root growth angle, seminal root numbers, and leaf area in the synthetic hexaploid wheat diversity panel - Maria Khalid; Zoya Khalid; Zubair Ahmed; Lee Hickey; Awais Rasheed; Alvina Gul; Rabia Amir (Plant Gene, 2025)

Synergism, biochemical changes and morphophysiological impacts induced by terpenes and phenylpropanoids in Sitophilus zeamais - Luciano de Souza; Maria das Graças Cardoso; Isaac Konig; Stefânia Priscilla de Souza; Ezequiel Garcia-Souza; Rosangela Cristina Marucci; Khalid Haddi (Pesticide Biochemistry and Physiology, 2025)

Insecticidal activity and morphophysiological disturbances of terpenes and phenylpropanoids poly(ε-caprolactone) nanoparticles in Drosophila suzukii and selectivity to Palmistichus elaeisis - Luciano de Souza; Maria das Graças Cardoso; Stefânia Priscilla de Souza; Cassia Duarte Oliveira; Rosangela Cristina Marucci; Juliano Elvis de Oliveira; Hallen Daniel Rezende Calado; Ezequiel Garcia-Souza; Isaac Konig; Khalid Haddi (Journal of Pest Science, 2025)

Failure of efficient cardiac proteostatic adaptations to chronic cAMP-stress is associated with accelerated heart aging - Maria Grazia Perino; Miguel Calvo-Rubio Barrera; Daniel R. Riordon; Giulio Agnetti; Alexander Maltsev; Admira Parveen; Christopher H. Morrell; Ismayil Ahmet; Khalid Chakir; Yelena S. Tarasova; Jia-Hua Qu; Kirill V. Tarasov; et al. (GeroScience, 2025)

Pollen morphology of cucurbitaceae using microscopic techniques for accurate taxa identification - Haleema Sadia; Khafsa Malik; Rahmatullah Qureshi; Khalid Mehmood; Khushdil Khan; Ahmad Hassan; Shabir Ahmad; Hussain Shah; Huma Gul; Jawaher Alkahtani; Bandar Mohsen Almunqedhi; Rashid Iqbal; et al. (Genetic Resources and Crop Evolution, 2025)

HIV mortality trends among the United States population, from 1999–2023: a CDC wonder database study - Abuoma Cherry Ekpendu; Muhammad Sohaib Asghar; Afsana Ansari Shaik; Muhammad Zain Khalid; Maria Duharte; Luis Duharte-Vidaurre; Moustafa Hegazi; Chad K. Brands (Infectious Diseases, 2025)

Band Gap Tuning in Mercaptoacetic Acid Capped Mixed Halides Perovskites and Effect of Solvents on Their Fluorescence Dynamics: A Potential Sensor for Polarity - Muhammad Asad Riaz; Usman Zahid; Maria Mukhtar; Muhammad Adnan Khalid; Muhammad Mubeen; Azhar Iqbal (Journal of Fluorescence, 2025)

Notes on species of Sporisorium and Ustilago from Pakistan - Sadiq Ullah; Najam-ul-Sehar Afshan; Aamna Ishaq; Maria Riaz; Muhammad Fiaz; Abdul Nasir Khalid; Mary Catherine Aime (Mycological Progress, 2024)

Biochemical, Physiological, and Nutrient Acquisition Response of Wheat Cultivars to Nickel and Vanadium Toxicity - Maria Tehseen; Houneida Attia; Abdul Khaliq; Muneera A. Saleh; Muhammad Zia Ul Haq; Khalid H. Alamer; Bader Ijaz; Iftikhar Ali; Shaista Perveen; Saddam Hussain (Journal of Plant Growth Regulation, 2024)

Phytochemical profile, nutritional and medicinal value of Nigella sativa - Shabbir Hussain; Aqsa Rukhsar; Munawar Iqbal; Qurat ul Ain; Jahanzaib Fiaz; Noman Akhtar; Maria Afzal; Naveed Ahmad; Iqbal Ahmad; Wissem Mnif; Muhammad Hashir Khalid (Biocatalysis and Agricultural Biotechnology, 2024)

In vivo evaluation of efficacy and safety of Coagulansin-A in treating arthritis - Sadaf Naz; Muhammad Usama Mazhar; Sidra Faiz; Maria Nawaz Malik; Jehan Zeb Khan; Ihsan Ul Haq; Lin Zhu; Muhammad Khalid Tipu (Toxicology and Applied Pharmacology, 2024)

Integrated Approach to Hydrogeochemical Assessment of Groundwater Quality in Major Industrial Zone of Punjab, Pakistan - Asmat Ali; Zahid Ullah; Nayab Ismaeel; Abdur Rashid; Warda Khalid; Maria Siddique; Javed Iqbal; Anwarzeb Khan; Muhammad Waqas; Junaid Ghani (Environmental Science and Pollution Research, 2024)

Elucidating the Mechanism of Copper-Induced Photoluminescence Quenching in 2-Phenylbenzimidazole-5-Sulfonic Acid - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Poshmal Sumreen; Mamoona Tabassum; Shoaib Ashiq; Sheikh Aadil Abbas; Raheel Akram; Azhar Iqbal (Journal of Fluorescence, 2024)

Geochemical Investigation of OCPs in the Rivers Along with Drains and Groundwater Sources of Eastern Punjab, Pakistan - Asmat Ali; Zahid Ullah; Maria Siddique; Junaid Ghani; Abdur Rashid; Warda Khalid; Muhammad Inayat Ullah Khan; Waqas Ashraf (Exposure and Health, 2024)

Risk assessment of trace element accumulation in soil and Brassica oleracea after wastewater irrigation - Ali Haider Shah; Muhammad Shahid; Maria Tahir; Natasha Natasha; Irshad Bibi; Tasveer Zahra Tariq; Sana Khalid; Muhammad Nadeem; Ghulam Abbas; Muhammad Farhan Saeed; Sabah Ansar; Camille Dumat (Environmental Geochemistry and Health, 2023)

Probing the Förster Resonance Energy Transfer Dynamics in Colloidal Donor-Acceptor Quantum Dots Assemblies - Muhammad Adnan Khalid; Muhammad Mubeen; Maria Mukhtar; Zumaira Siddique; Poshmal Sumreen; Firdevs Aydın; Demet Asil; Azhar Iqbal (Journal of Fluorescence, 2023)

Integrating of electrocoagulation process with submerged membrane bioreactor for wastewater treatment under low voltage gradients - Khalid Bani-Melhem; Maria Elektorowicz; Muhammad Tawalbeh; Abeer Al Bsoul; Ahmed El Gendy; Hesam Kamyab; Mohammad Yusuf (Chemosphere, 2023)

Experimental study of the effects of salinity on nanoparticle-surfactant foams for fracture stimulation application - Tuan Tran; Maria Elena Gonzalez Perdomo; Manouchehr Haghighi; Khalid Amrouch (Gas Science and Engineering, 2023)

Storm surge and tsunami deposits along the Moroccan coasts: state of the art and future perspectives - Otmane Khalfaoui; Laurent Dezileau; Nadia Mhammdi; Fida Medina; Meryem Mojtahid; Otmane Raji; Hajar El Talibi; Samira Mellas; Jean-Philipe Degeai; Khalid El Khalidi; Maria Snoussi; Zourarah Bendahhou; et al. (Natural Hazards, 2023)

Recent trends in management strategies for two major maize borers: Ostrinia nubilalis and Sesamia nonagrioides - Gülay Kaçar; Ana Butrón; Dimitrios Kontogiannatos; Peng Han; Maria Fernanda G. V. Peñaflor; Gema P. Farinós; Fangneng Huang; William D. Hutchison; Bruno H. S. de Souza; Rosa Ana Malvar; Anna Kourti; Ricardo Ramirez-Romero; et al. (Journal of Pest Science, 2023)

A comprehensive health effects assessment of the use of sanitizers and disinfectants during COVID-19 pandemic: a global survey - Fallah Hashemi; Lori Hoepner; Farahnaz Soleimani Hamidinejad; Daniela Haluza; Sima Afrashteh; Alireza Abbasi; Elma Omeragić; Belma Imamović; Narin A. Rasheed; Taqi M. J. Taher; Fitri Kurniasari; Dhuha Youssef Wazqar; et al. (Environmental Science and Pollution Research, 2023)

Bubalus bubalis Blood as Biological Tool to Track Impacts from Cobalt: Bioaccumulation and Health Risks Perspectives from a Water-Soil-Forage-Livestock Ecosystem - Maria Ghazzal; M. Iftikhar Hussain; Zafar Iqbal Khan; Kafeel Ahmad; Mudasra Munir; Bilal Ahamad Paray; Mohammad Khalid Al-Sadoon (Biological Trace Element Research, 2023)

Correction to: Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Multivariate characterization of biochemical and physiological attributes of quinoa (Chenopodium quinoa Willd.) genotypes exposed to nickel stress: implications for phytoremediation - Maria Aslam; Mbarki Sonia; Ghulam Abbas; Muhammad Shahid; Behzad Murtaza; Muhmmad Shafique Khalid; Saeed Ahmad Qaisrani; Hesham F. Alharby; Sameera A. Alghamdi; Basmah M. Alharbi; Yinglong Chen (Environmental Science and Pollution Research, 2022)

Correction to: Tracing in vivo the dorsal loop of the optic radiation: convergent perspectives from tractography and electrophysiology compared to a neuroanatomical ground truth - Michele Rizzi; Ivana Sartori; Maria Del Vecchio; Luca Berta; Domenico Lizio; Flavia Maria Zauli; Alessandro De Benedictis; Silvio Sarubbo; Khalid Al-Orabi; Valeria Mariani; Pietro Avanzini (Brain Structure and Function, 2022)

Diversity of bacterial pathogens and their antimicrobial resistance profile among commensal rodents in Qatar - Md Mazharul Islam; Elmoubashar Farag; Mohammad Mahmudul Hassan; Khalid A. Enan; K. V. Mohammad Sabeel; Maryam Mohammed Alhaddad; Maria K. Smatti; Abdulla Mohammad Al-Marri; Abdul Azia Al-Zeyara; Hamad Al-Romaihi; Hadi M. Yassine; Ali A. Sultan; et al. (Veterinary Research Communications, 2022)

Tracing in vivo the dorsal loop of the optic radiation: convergent perspectives from tractography and electrophysiology compared to a neuroanatomical ground truth - Rizzi Michele; Sartori Ivana; Del Vecchio Maria; Berta Luca; Lizio Domenico; Zauli Flavia Maria; De Benedictis Alessandro; Sarubbo Silvio; Al-Orabi Khalid; Mariani Valeria; Avanzini Pietro (Brain Structure and Function, 2022)

Elucidating the Photoluminescence Quenching in Ensulizole: an Artificial Water Soluble Sunscreen - Muhammad Mubeen; Muhammad Adnan Khalid; Maria Mukhtar; Saba Shahrum; Shanila Zahra; Saima Shabbir; Azhar Iqbal (Journal of Fluorescence, 2021)

Site-specific deterministic and probabilistic tsunami hazard assessment for Diba-Oman and Diba-Al-Emirates - Issa El-Hussain; Zaid Al-Habsi; Khalid Al Bloushi; Rachid Omira; Ahmed Deif; Maria Ana Baptista; Adel M. E. Mohamad (Arabian Journal of Geosciences, 2021)

Synthesis, Structure Study, First-Principles Investigations and Luminescence Properties of Europium and Terbium Complexes - Bakhat Ali; Helio A. Stefani; Muhammad Imran; Ahmad Irfan; Mohammed A. Assiri; Maria Claudia F. C. Felinto; Muhammad Khalid; Abdullah G. Al-Sehemi (Journal of Fluorescence, 2020)

Analyzing the occurrence of floods and droughts in connection with climate change in Punjab province, Pakistan - Syeda Maria Ali; Bushra Khalid; Asma Akhter; Aneeza Islam; Shahzada Adnan (Natural Hazards, 2020)

Understanding Conformational Dynamics of Complex Lipid Mixtures Relevant to Biology - Ran Friedman; Syma Khalid; Camilo Aponte-Santamaría; Elena Arutyunova; Marlon Becker; Kevin J. Boyd; Mikkel Christensen; João T. S. Coimbra; Simona Concilio; Csaba Daday; Floris J. van Eerden; Pedro A. Fernandes; et al. (The Journal of Membrane Biology, 2018)

Abscisic acid and salinity stress induced somaclonal variation and increased histone deacetylase (HDAC) activity in Ananas comosus var. MD2 - Nur Asniyati Abdul Halim; Boon Chin Tan; Mohd Razik Midin; Maria Madon; Norzulaani Khalid; Jamilah Syafawati Yaacob (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Single and Combined Impacts of Vitamin A and Selenium in Diet on Productive Performance, Egg Quality, and Some Blood Parameters of Laying Hens During Hot Season - Mohamed E. Abd El-Hack; Khalid Mahrose; Ali A. Askar; Mahmoud Alagawany; Muhammad Arif; Muhammad Saeed; Farzana Abbasi; Rab Nawaz Soomro; Farman Ali Siyal; Maria Tabassum Chaudhry (Biological Trace Element Research, 2017)

Alleviating the environmental heat burden on laying hens by feeding on diets enriched with certain antioxidants (vitamin E and selenium) individually or combined - Mohamed E. Abd El-Hack; Khalid Mahrose; Muhammad Arif; Maria Tabassum Chaudhry; Islam M. Saadeldin; Muhammad Saeed; Rab Nawaz Soomro; Imtiaz Hussain Raja Abbasi; Zaib Ur Rehman (Environmental Science and Pollution Research, 2017)